2008
DOI: 10.1007/s11013-008-9115-1
|View full text |Cite
|
Sign up to set email alerts
|

The Construction of “Cultural Difference” and Its Therapeutic Significance in Immigrant Mental Health Services in France

Abstract: Since the early 1970s, the French public health system has been accorded considerable responsibility for immigrants identified by the educational, judicial or social service authorities as psychologically distressed or socially disruptive. In this paper we discuss three models of healing embedded in constructs of "cultural difference" and addressed at specialized mental health-care centers catering to immigrants in Paris: "cultural mediation," transcultural psychiatry/ethnopsychiatry and clinical medical anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 10 publications
0
20
1
1
Order By: Relevance
“…While many cultural competence advocates see themselves at the forefront of an antiracist movement and seek to extend this awareness to others, they simultaneously acknowledge their limited ability to address the structural factors that determine the health disparities that opened this movement (e.g., Chapman and Berggren 2005; Krieger et al 2005; Sargent and Larchanché 2009). Another speaker at the same roundtable observed that most “awareness tools” focus on being comfortable with and knowledgeable about different cultural groups, which she worried “might take attention away from what we really need to do to address the underlying factors” in health disparities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While many cultural competence advocates see themselves at the forefront of an antiracist movement and seek to extend this awareness to others, they simultaneously acknowledge their limited ability to address the structural factors that determine the health disparities that opened this movement (e.g., Chapman and Berggren 2005; Krieger et al 2005; Sargent and Larchanché 2009). Another speaker at the same roundtable observed that most “awareness tools” focus on being comfortable with and knowledgeable about different cultural groups, which she worried “might take attention away from what we really need to do to address the underlying factors” in health disparities.…”
Section: Resultsmentioning
confidence: 99%
“…Because they stem from different intellectual lineages, CC frameworks represent both universalizing and particularizing tendencies (e.g., Dorazio-Migliore et al 2005; Dysart-Gale 2006; Kowal 2008; Lo 2010). In their ethnography of mental health services for migrants in France, for example, Sargent and Larchanché (2009) outline three approaches to cultural competence in psychiatric care that are meant to address perceived cultural differences among West and North African migrants. While many state-run mental health clinics utilize the notion of cultural difference in developing effective therapies, they are governed by a French state deeply embedded in the ideals of equality and universalism.…”
Section: Hybrid Formations Of Cultural Expertisementioning
confidence: 99%
See 1 more Smart Citation
“…First, our aim is not to document or propose any specific pedagogical models or ''best practices, '' but Cult Med Psychiatry (2013) 37:241-252 243 rather to present complex, multi-faceted portraits of four long-standing programs whose successes and failings provide valuable insight into the everyday life of ''culture'' in clinical education and clinical research training. Second, we are indebted to earlier contributions and analyses by anthropologists and cultural psychiatrists (Desjarlais et al 1995;Good 1977Good , 1994Good and Good 1980;Guarnaccia and Rodriguez 1996;Kleinman 1980;Kleinman and Good 1986;Lakes et al 2006;Sargent and Larchanché 2009), especially those that critique reductive approaches to the culture concept and instead advance a process-oriented, anthropologically-informed conception of culture (Carpenter-Song et al 2007;Gregg and Saha 2006;Kirmayer 2012b;Kleinman and Benson 2006;Taylor 2003). Contributors to the collection are especially sensitive to the fact that ''culture'' is often deployed as either a euphemism or an empty category.…”
Section: The Collection: Structure and Distinguishing Featuresmentioning
confidence: 95%
“…This issue is not confined to the UK and reflects fundamental differences across national, cultural, ethnic and religious groups in the way mental distress and illness is understood and defined, and related to expectations of recovery and treatment [19,20]. Canales et al describe ‘narrative interaction’, sharing of personal stories, as a form of therapeutic communication that permits the gendering of inequalities to be addressed in nursing practice [12].…”
Section: Introductionmentioning
confidence: 99%